PROBLEMS OF TEACHING LISTENING SKILLS - Giyozova, Sabina (MMIT Proceedings, 2023)
In this research paper I have covered my findings in time of research made on the issue of teaching listening. Here I have given several examples for each of my opinions and I tried to prove them with scholars' points of view. This research paper would come in handy for whom are carrying out the research work in the field of teaching English skills to young learners. The instruments of this research are observation, interview and questionnaire. In short, the results of this research showed that teacher’s difficulties divided into two factors, those are internal and external factors. Internal factors which came from the respondent himself such as; he feels the difficulties in teaching, preparing listening materials, choosing method, technique, and strategy. External factors are: sound from environment activities like woodcutter machine, module, media problem as cable injector of sound system to laptop, English laboratory, electric off.